An investigation into the value of supplementing dissection of the human body with alternative resources: Perceptions of students and staff at the University of Cape Town - Ramgoolam, Shakira (Division of Clinical Anatomy and Biological Anthropology, 2017)
The purpose of this study was to explore the perceived value of supplementing the traditional cadaver dissection course at the University of Cape Town's Faculty of Health Sciences (UCT FHS) with alternatives in order to aid students in their learning of anatomy. The study aimed to collect information which could be used to provide insight into facilitating a deeper educational experience for students and teachers alike in the future with the aim of better retention of knowledge over time. The intention of the study was to obtain results which could potentially provide insight into the feasibility of adopting a contemporary view on anatomy education at UCT FHS and thus inform the anatomy course in the future by acquiring feedback directly from the students and staff of the university. Data was collected by way of a 22 question survey delivered to second to sixth year MBChB students as well as the staff and postgraduate students at UCT FHS. The survey was entirely voluntary. A total of 190 complete responses were collected. The results of the study indicate that both staff and students feel that the cadaver dissection course is an irreplaceable part of the curriculum, and if the faculty chose to use any technological alternatives to teach anatomy, that they should supplement and not replace traditional dissection. Furthermore, the study showed that the staff and students are comfortable with technology in general, and are open to the use of various technologies such as online material, virtual software, media sites, applications and the like in order to bolster their learning. These results may provide insight into the viability of adopting a contemporary view on anatomy education at UCT FHS and may thus inform changes to the anatomy curriculum in the future.